2021
DOI: 10.3390/cancers13040822
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Cell Communication: From Tumour-Derived Exosomes and Their Role in Tumour Progression to the Use of Exosomal Cargo for Cancer Treatment

Abstract: Exosomes are nano-vesicle-shaped particles secreted by various cells, including cancer cells. Recently, the interest in exosomes among cancer researchers has grown enormously for their many potential roles, and many studies have focused on the bioactive molecules that they export as exosomal cargo. These molecules can function as biomarkers in diagnosis or play a relevant role in modulating the immune system and in promoting apoptosis, cancer development and progression. Others, considering exosomes potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 185 publications
(222 reference statements)
0
37
0
Order By: Relevance
“…Finally, it has been identified that exosomes can control tumor growth due to certain specific proteins and RNAs that are transferred to malignant cells. This shows the role of exosomes as biological reprogrammers of tumor cells [242]. It has been shown that the exosomal transfer of miR-139-5p into bladder cancer cells has role in regulating tumorigenesis.…”
Section: Potential Role Of Exosomes In Cancer Treatmentmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, it has been identified that exosomes can control tumor growth due to certain specific proteins and RNAs that are transferred to malignant cells. This shows the role of exosomes as biological reprogrammers of tumor cells [242]. It has been shown that the exosomal transfer of miR-139-5p into bladder cancer cells has role in regulating tumorigenesis.…”
Section: Potential Role Of Exosomes In Cancer Treatmentmentioning
confidence: 81%
“…Numerous studies have aimed to evaluate exosomes as potential delivery systems for chemotherapeutics with anticancer properties, and as biological reprogrammers of cancer cells [242]. Thus, Han D, et al compared the antitumoral efficacy of paclitaxel encapsulated by electroporation in natural killer cell-derived exosomes (PTX-NK-Exos) as compared with free paclitaxel (PTX).…”
Section: Potential Role Of Exosomes In Cancer Treatmentmentioning
confidence: 99%
“…The capacity of DCexos to prime T cells-especially antigen-specific CD8 T cells-and their ability to shuttle different biomolecules, including proteins (such as antigens and cytokines) and RNAs to modulate immune responses, coupled with their amenability to modification of their composition and cargos, have presented DCexo-based vaccines as much improved alternative to DC cell-based vaccines [44,[71][72][73][74]. Additionally, DCexos possess other advantages over DC(cell)-based vaccines.…”
Section: Dc-derived Exosomes and Their Functionmentioning
confidence: 99%
“…Tumor cell-secreted cytokines, growth factors, and EVs can reshape the extracellular matrix, regulate and reprogram the microenvironment of LNs and other distant organs, and provide a suitable niche for the spread of tumor cells (44)(45)(46). TEVs are considered to inhibit innate immune responses by mobilizing bone marrow mesenchymal stem cells and activating tumorrelated macrophages and neutrophils (47).…”
Section: Evs and Pre-metastatic Nichementioning
confidence: 99%